2004
DOI: 10.1089/0897715041953803
|View full text |Cite
|
Sign up to set email alerts
|

Inaccurate Early Assessment of Neurological Severity in Head Injury

Abstract: Intubation, which requires sedation and myorelaxants, may lead to inaccurate neurological evaluation of severely head-injured patients. Aims of this study were to describe the early clinical evolution of traumatic brain injured (TBI) patients admitted to intensive care unit (ICU), to identify cases of over-estimated neurological severity, and to quantify the risk factors for this over-estimation. A total of 753 TBI patients consecutively admitted to ICU of three academic neurosurgical hospitals (NSH) were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 9 publications
0
42
0
8
Order By: Relevance
“…As a result, the ability to obtain an accurate assessment of the GCS is compromised (Stocchetti et al, 2004). In a recent survey of 17 major trauma centers in the United States, most centers evaluated the GCS within 1 h of admission, and neurosurgeons indicated that hypoxia and hypotension are stabilized before the scoring the initial GCS (Marion and Carlier, 1994).…”
Section: The Glasgow Motor Score-a Moving Targetmentioning
confidence: 99%
“…As a result, the ability to obtain an accurate assessment of the GCS is compromised (Stocchetti et al, 2004). In a recent survey of 17 major trauma centers in the United States, most centers evaluated the GCS within 1 h of admission, and neurosurgeons indicated that hypoxia and hypotension are stabilized before the scoring the initial GCS (Marion and Carlier, 1994).…”
Section: The Glasgow Motor Score-a Moving Targetmentioning
confidence: 99%
“…1 The GCS has important limitations, particularly in patients who are intoxicated or who require pharmacologic sedation or paralysis. 2 Although GCS correlates with survival and functional outcome, the correlation is weak and inconsistent. [3][4][5][6] Since the 1980s, most patients with traumatic brain injury (TBI) are also evaluated with computerized tomography (CT) scans, and experienced clinicians use anatomic findings from CT scans in conjunction with GCS scores and other clinical information to assess injury severity and plan surgical or medical interventions.…”
mentioning
confidence: 99%
“…In patients having SDH (25% of total), 40 patients (44.44%) had poor outcome. (19)(20)(21)(22)(23)(24) Moderate (11)(12)(13)(14)(15)(16)(17)(18) Severe ( In this study, the mean GCS score was 10.61 .110 patients had a GCS score 8 or less (31.42%). 80of those patients (72.72%) had GOS V score.…”
Section: Resultsmentioning
confidence: 62%
“…( Stocchetti N et al; The RTS correlates well with the probability of survival. It also used for assessing prognosis if the RTS on arrival is compared to the best RTS after resuscitation.…”
Section: Introductionmentioning
confidence: 97%